International Symposium on Zeolites and Microporous Crystals 2015. Issue 1 (1st January 2016) - Barrow, Nathan
The International Symposium on Zeolite and Microporous Crystals 2015 (ZMPC2015) was held at the Sapporo Convention Center, Japan, from 28th June to 2nd July 2015 and had 435 attendees from 32 countries, with 75% from Japan, China, Korea or Taiwan. 396 presentations covered all aspects of zeolites and microporous crystals over four days. Catalysis and synthesis were the two main themes (46% of all presentations) with the others being: new porous materials; membranes and films; adsorption and diffusion; characterisation; novel applications; industrial applications; layered materials; computational chemistry; post-synthetic treatment; crystallography; and ion exchange. There were six plenary talks along with 17 keynote and 94 oral presentations that took place in three parallel sessions. There were two poster sessions for 250 posters and recent research reports.